Influence of electron transport media on the performance of MEMS-based microbial fuel cell. (November 2021) - Huang, Song-Jeng; Ubando, Aristotle T.; Xu, Bo-Kay; Culaba, Alvin B.; Lin, Yu-An; Wang, Chin-Tsan
Abstract: Microbial fuel cells (MFCs) are recognized as an efficient method to utilize biomass to generate power while simultaneously treats wastewater. Micro-electro-mechanical system (MEMS) technology enables miniaturization of the MFCs system. Miniaturized MFCs through MEMS strengthen the system's reaction capacity that makes it suitable for environmental sense field applications such as sensors or biomedical actuators. In this work, MEMS technology is employed to deposit metal layers on the surface of the anode/cathode electrode to enhance the power density of the MFC. Hence, micromixers and micro-pillars in the anode tank along with the influence of the electron transport media on MFC performance were evaluated. The introduction of the micro-mixers promotes the full mixing of the anolyte. The inclusion of the micro-pillars increases the surface area of the electrode, thereby enhancing the electrical energy output of the MFC. Results revealed that the introduction of the microstructure and the electron transfer media to the anolyte in the MFC have yielded a maximum current of 66.55 μ A cm −2, a maximum power density of 3.28 μ W cm −2, and an internal resistance value of 2 . 57 k Ω . Moreover, the inclusion of several micro-mixers and micro-pillar structures to the anode tank has shown the performance enhancement of MFC. Relevant research results will provide a reference for future research on the combination of MFCs and sensors.